Supervisão acadêmica do Projeto Mais Médicos para o Brasil - Alves, Daiana Cristina Machado (2019)
In 2012, a new version of PNAB was published, which expands AB's perspective, since it takes responsibility under the development of integral care, defines that Family Health is the strategy of expansion, qualification and consolidation of health care . However, the new guidelines of the PNAB 2012 regarding the format of the team with the parameterization of the doctors' workload were not enough to solve the difficulty of recruiting and fixing the professionals in the FHS in regions of great vulnerability. In the attempt to overcome the issue of providing health professionals, especially in the regions of Brazil with difficulties of attraction and fixation, over the years programs of provision were implemented. In 2013, the Federal Government created the "Mais Médicos" Program (PMM) in order to reduce the shortage of doctors in the different regions, to combat inequalities in access to basic health care, to improve medical education in the country and to strengthen health policy. education with teaching-service integration. The program was structured in three axes of action. The third, entitled "More Doctors" Project for Brazil (PMMB), was to provide emergency medical care in vulnerable areas and had as one of its objectives to strengthen the policy of permanent education with the integration of teaching and service, through the public institutions of higher education in the academic supervision of the activities developed by physicians. The purpose of this study was to understand the potentialities and limits of PMMB academic supervision in the development of pedagogical processes, to describe the concepts and conceptions presented about academic supervision and to identify the way academic supervision is done using the methodologies used. The literature review method was used to select the empirical material. Eleven studies published in the period from 2013 to 2018 were selected from the Scientific Electronic Library Online (SciELO), Lilacs, Portal Capes, Virtual Health Library (VHL-APS) and the Knowledge Platform of the More Doctors Program. The thematic categories selected after the analysis of the studies were: The Academic Supervision of the Project More Doctors for Brazil and its conceptions; Academic Supervision: a political - institutional process; Academic Supervision and its technical dimension; Academic Supervision and its pedagogical dimension. The findings show that supervision is conceived as a practice that offers support horizontally and values ​​the exchange of experience. The MEC chose to form a team of institutional supporters to act in the states in order to support with tutors and supervisors in the development of activities. It has been carried out through the use of active methodologies such as pedagogy of problematization, wheels of conversations, pedagogical tools Balint-Paidéia. The limits and potentialities of AS were evidenced. According to the ways of doing of the supervision can be affirmed that this is a strategy that can strengthen the policy of permanent education in basic attention.